KRIVORIZHYA – A PROSPECTIVE REGION FOR THE DESIGN OF HOTELS ORGANIZED BY INDUSTRIAL TOURS - Довбаш, Анна; Шидловская, Елена; Ищенко, Татьяна; Медведь, Ирина (SWorldJournal, 2021)
To date, the latest innovative achievements in the field of hospitality are: bleisure-travel, eco-travel, industrial tourism, the use of artificial intelligence, robots, chatbots and more. Among this is industrial tourism, which, in fact, is a very specia